Problematising the Dominant Child Rights Discourses: Why We Need a Nuanced Approach to Combat Child Labour - Mohammed, Abdul-Rahim; Achanso, Adams Sulemana (Advances in Social Sciences Research Journal, 2021)
Three decades have now passed since the promulgation of the United Nations Convention on the Rights of the Child (CRC) in 1989. Despite the almost universal ratification of the CRC, as well as the heightened global awareness of the prevalence of child labour, the phenomenon persists. Following the ratification of the CRC, the rights-based approach to combating child labour became the dominant theoretical perspective. By problematising the dominant child-rights framework, this paper contributes to the discourse on child labour by arguing for a more nuanced approach to addressing the phenomenon. The paper achieves this objective by underscoring the importance of understanding and engaging with the reasons why children work, the socio-economic contexts within which they work, and why policies designed to address child labour should address the structural barriers that directly and indirectly promote child labour.